To have your cake and eat it too: accountability under a preferential voting system - Mikulska, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
Informed by the findings in the economic voting literature and using an original dataset on Polish elections this research breaks away from this established practice and goes a step further by showing how economic conditions allow voters to distinguish between high/low performers and effectively attribute responsibility under open-list PR systems where voters can choose not only among parties but also among individual candidates. By integrating open-list design into the model of accountability this study transforms the way we think about the very act of voting.